Physical Performance and Morphological Characteristics of Young Basketball Players before and after COVID-19 - Vladan Pelemiš; Dajana Zoretić; Ivan Prskalo (MDPI AG, 2023)
The aim of this study was to determine possible changes in physical performance and morphological characteristics in young basketball players before and after quarantine caused by COVID-19. The research was conducted on a total sample of 46 young basketball players. Participants were measured before the quarantine and pandemic in January 2020 and then after the quarantine period, one year later in March 2021. The results indicate the existence of significant differences in total muscle mass (p < 0.01) in favor of higher values measured before quarantine. Moreover, total fat percentage was higher (p < 0.03) after quarantine. As for physical performance, significant differences were also observed in the counter movement jump test (p < 0.05) and the 20 m shuttle run test (p < 0.05), with significantly poorer results for the group of participants measured after quarantine. The authors conclude that the consequences of the quarantine and pandemic of the SARS-CoV-2 virus were definitely negative, as higher values of body fat and lower values of the percentage of total muscle mass were observed. In addition, a lower level of the explosive power of lower limbs was observed, accompanied by lower aerobic endurance in young basketball players.